Pengaruh Kecemasan dan Kepercayaan Diri Terhadap Prestasi Belajar Mahasiswa Pendidikan Matematika STKIP PGRI Pacitan - Urip Tisngati; Nely Indra Meifiani (Jurnal Penelitian Pendidikan, 2014)
This was a quantitative study which was ex post facto in nature. The data collectinginstruments consisted of a questionnaire and a mathematics learning achievement test.The results of the study show that: 1) there are not effects together of self confidenceand students’ anxiety towards Mathematics as an aggregate on Mathematics learningachievements; 2) there are relationship between self confidence and students Mathematicslearning achievements.